2012
DOI: 10.1111/j.1742-6723.2011.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I does not independently predict mortality in critically ill patients with severe sepsis

Abstract: Critically ill patients with severe sepsis who had elevated troponin had increased hospital and intensive care mortality. However, cardiac troponin I did not independently predict hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
2
23
1
5
Order By: Relevance
“…However, our findings are in contrast with the study of Rosjo et al and Triuvoipati,16 17 who found that hs-cTnT was not an independent predictor of mortality in ICU patients with septic shock. This discrepancy is probably caused by the differences in patient populations and the different troponin assay used.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our findings are in contrast with the study of Rosjo et al and Triuvoipati,16 17 who found that hs-cTnT was not an independent predictor of mortality in ICU patients with septic shock. This discrepancy is probably caused by the differences in patient populations and the different troponin assay used.…”
Section: Discussioncontrasting
confidence: 99%
“…Quando ocorre um dano à célula do miocárdio, a troponina é liberada na circulação e pode ser mensurada por meio de métodos de imunoensaio (Hamacher et al, 2015;Sheyin et al, 2015;Tiruvoipati et al, 2012). No atual estudo, as concentrações séricas da troponina I cardíaca não demonstraram diferença estatística significativa entre o grupo controle e o grupo piometra sepse ou não sepse, diferindo de Pelaner et al (2008), em que houve diferença significativa na concentração da troponina I em cadelas com piometra se comparadas ao grupo controle.…”
Section: Methodsunclassified
“…A troponina I é uma proteína encontrada em fibras musculares esqueléticas e cardíacas responsáveis pela contração muscular (Hamacher et al, 2015;Sheyin et al, 2015;Tiruvoipati et al, 2012). A troponina I cardíaca é encontrada apenas no coração, sendo expressa exclusivamente pelo miocárdio, e está especialmente associada às miofibrilas, embora pequenas quantidades estejam presentes também no citosol (Dunn et al, 2008).…”
Section: Introductionunclassified
See 2 more Smart Citations